Globalization and Protest Expansion. (7th February 2015) - Dodson, Kyle
Abstract: Evidence of protest expansion both in the United States and abroad has stimulated theoretical discussion of a "movement society, " with some arguing that protest activities are becoming a standard feature of democratic politics. In advancing this claim, many have highlighted the role of domestic factors—for example, generational change or economic affluence—without fully accounting for the possibility that international dynamics may play an important role as well. The lack of work is surprising not only because the trend in protest is international in scope, but also because work in comparative sociology suggests globalization may make an important contribution. This study addresses the empirical gap by examining how political globalization (as measured by memberships in international organizations) and economic globalization (as measured by trade activity and foreign investment) influence trends in protest participation. Using data from World Values Surveys of 37, 716 respondents in 17 advanced democracies merged with data on several national and international indicators, this study examines how the probability of participating in protest has changed over time as a result of these two forms of globalization. The results of multivariate, multilevel analysis combined with simulations indicate that trends in political globalization have expanded protest activity, while trends in economic globalization have limited that expansion. These results suggest that social movement scholarship should continue to examine the implications of globalization for protest behavior and other social movement dynamics. La evidencia sobre la expansión de la protesta, tanto en Estados Unidos como en el extranjero ha estimulado el debate teórico de un "movimiento de la sociedad" y algunos sostienen que las protestas están convirtiendose en una característica estándar de la política democrática. Al afirmar esto, muchos han puesto de relieve el papel que juegan los factores internos -como por ejemplo el cambio generacional o la riqueza económica- sin tomar plenamente en cuenta la posibilidad de que las dinámicas internacionales puedan desempeñar un papel importante también. La falta de estudios en esta área es sorprendente no sólo porque la tendencia de las protestas es de alcance internacional sino también porque estudios de sociología comparada sugieren que la globalización puede ser un factor relevante para entender estos fenómenos. El artículo aborda este vacío empírico y analiza la influencia tanto de la globalización política (medida por membresías en organizaciones internacionales) como de la globalización económica (medida por el comercio y la inversión extranjera) en la participación social en protestas. El estudio utiliza los datos de la Encuesta de Valores Globales (World Values Surveys) que cuenta con 37, 716 encuestados en 17 democracias avanzadas junto con datos sobre varios indicadores nacionales e internacionales para examinar cómo la probabilidad de participar en una protesta ha cambiado a través del tiempo como resultado de estas dos formas de globalización. Los resultados del análisis multivariado y multinivel en combinación con simulaciones indican que las tendencias de la globalización política han ampliado las actividades de protesta, mientras que las tendencias de la globalización económica han limitado esta expansión. Los resultados sugieren que los estudios sobre movimientos sociales deben seguir examinando las implicaciones de la globalización tanto para el funcionamiento de las protestas como para entender otras dinámicas propias de estos movimientos.